Keberkesanan program latihan keselamatan di kalangan pekerja kilang elektronik. Kajian kes di Perbadanan Produktiviti Negara (NPC) cawangan Sarawak - Andriana Maureen, anak Anthony Toni. (Universiti Malaysia Sarawak (UNIMAS), 2002)
Generally, this study aims to indentify participants 'perception towards the effectiveness ofsafety training programme and the factors influencing the effectiveness oftraining programme. The factors studied were evaiualion tools, trainer, content, equipment, time management dall strategy of learning. Besides, this study also aims to determine difJerences based on demograpic factors (sex, age, race, education level and the length ofservice) and perception towards the effectiveness oftraining programme. Questionnaire was used as an instrument ofthe study to gain participants' response towards training program. This study con.sisls of all the participants in the training programme, which is equivalent to 42 participants. Descriptive statistics is used to present the findings 0/ demographic features, while for the inferential statistics, T-test, One-Way Analysis of Variance (ANOVA) and Pearson Correlation test are used. The ttest and One-Way ANDVA are used to determine the significant difJerences between demographic factors ofrespondents and the perception towards the effectiveness oftraining programme. This research finding also shows that demographic characteristics such as sex (t=0.009, p=0.924), age (F=I.683, p=0.187), race (F=I.123, p=0.360) and the length of service (F=I.434, p=0.248) do not show any significant between participants' perception towards the effectiveness oftraining programme whereas education level features (F=3.908, p=0.016) do influence participants' perception towards the effectiveness oftraining pragramme. Besides, Pearson Correlation test is used to determine the relationship between the factors and participants' perception towards the effectiveness oftraining programme. There are no significant relationship between the factors of evaluation tool (r=0.030, p=0.850), content (r=0.240, p=0.126), equipment (0.218, p=0.166) and strategy of learning (r=0.016, p=0.921) and particpants' perception towards the effectiveness oftraining programme. Furthermore, the result ofthis research also shows that there is significant relationship between trainer and time management (r=-0.307*, p=0.048) with participants' perception towards the effectiveness ofsafety training programme. In conc/usion, the result ofthis research shows that the factors such as evaluation, trainer, content, equipment, time management and strategy oflearning, and the participants' perception should be given serious attention in order to increase the effectiveness of safety training programme. The organization should evaluate the training programme before, during and after its implementation in order to ensure its effectiveness.